Evaluación Nutricional y autopercepción de la imagen corporal en estudiantes de la Universidad Técnica del Norte. Ecuador: Nutritional assessment and body image self-perception in “Técnica del Norte” University students, Ecuador (La U Investiga, 2020)
The objective of the research was to relate the self-perception of body image and the nutritional status of the UTN students. Non-experimental, correlational and cross-sectional study in 132 students. Nutritional evaluation was performed using BMI, % body fat, Waist Circumference and Somatotype; body self-perception with anatomical models. Pregnant women and students with physical disabilities were excluded. It was found 28% men, 72% women. According to BMI, 64% are of adequate weight, 4% are underweight and 32% are overweight. According to percentage of body fat, 12% optimal nutritional status, 52% body fat that indicates overweight and obesity. 39% cardiovascular risk according to waist circumference. The most prevalent somatotype is the meso-endomorph and mesomorphendomorph. Self-perception of body image reflects: men and women identify with a figure that indicates normal BMI (64%), there are no students who identify with anatomical models that indicate low weight. Males have a greater affinity for the larger anatomical model, while women for the more linear. Men have a higher BMI in relation to women according to self-report. women perceive their body image more accurately than men. 2.7% of men look thinner than they are and 37.8% look fatter. 11.6% of women look thinner than they are and 25.3% perceive themselves as fatter. Conclusion: In this group there is a relationship between self-perception of body image and nutritional status determined by anthropometry.
Keywords: nutritional status; body mass index; body fat percentage; somatotype; body image